Evaluation of effects of climatic factors on acute myeloid leukemia at Hiwa Hospital Sulaymaniah Iraq - Karim, Dr. Sozan Qadir Karim; Zangana, Dr. Bushra Qadir Kareem Zangana (Sulaimani Journal for Humanities, 2025)
Recent studies have suggested seasonal variation in the diagnosis of acute myeloid leukemias (AML). Some studies have proposed that seasonal factors may play a role in etiology of this group of hematological neoplasms, but the exact association to atmospheric elements is still not clearly understood. Here, we prospectively evaluated potential seasonality of AML diagnosis among adults and children whose place of settlement was Sulaymaniyah city. Cases included in this study, were diagnosed over five years from 2019-2023 and admitted to Hiwa Hospital which is a tertiary hematology-oncology care unit in that city. Climatic elements for all the respective seasons were obtained for the years of the study from Sulaymaniyah Metrological and Earthquake Center. Pearson correlation and multiple regression analysis were used to detect possible seasonal variation. Seasons of peak diagnoses were Spring followed by Autmn. Our data showed some variation between males and females, males were more affected than females. Among the various age groups, age between 18-63 are more affected. According to the statistical analysis, climatic variables had 26.3% effects on the disease, especially sun shine, temperature and wind speed which have a positive correlation. Conversely, negative effects were found between humidity and precipitation with the disease.
Keywords: Seasons; climatic variables; acute myeloid leukemia; immunity